The prospects of interleukin-6 inhibition in rheumatoid arthritis: Olokizumab (novel monoclonal antibodies to IL-6) - E. L. Nasonov; E. Feist (Научно-практическая ревматология)
Rheumatoid arthritis (RA) is a chronic immune-mediated rheumatic diseases (IMRDs) manifested with progressive destruction of joints, systemic inflammation of visceral organs and a wide range of co-morbidities associated with chronic inflammation. Among the cytokines involved in the pathogenesis of RA and certain other IMRDs, the role of interleukin (IL) 6 is of special interest. The introduction of mAbs tocilizumab (TCZ) and later sarilumab (SAR), both blocking the receptor of this cytokine, into clinical practice was an important achievement in the treatment of IIRDs at the beginning of the 21st century. As a novel approach in the treatment of RA, the humanized mAb against IL-6 olokizumab (OKZ) is in development by the Russian company R-PHARM under the license agreement with UCB Pharma. The review examines new data on efficacy and safety of OKZ in RA and the prospects of its use in rheumatology